Genetic Characteristics of the Env Regions in HIV-1-Infected Subjects in Baoding City, Hebei Province, China - Geng, Kunjing; Wei, Wenchao; Chen, Sisi; Shi, Haoxi; Fan, Weiguang (Current HIV research, 2024)
The envelope glycoprotein (Env) on the surface of the human immunodeficiency virus (HIV-1) is a crucial protein that mediates binding to host cell receptors and subsequent membrane fusion. Env, as the sole target for neutralizing antibodies, holds unique importance in vaccine design. Therefore, analyzing the genetic characteristics of the Env region offers reference data for vaccine and drug design. From December 2021 to December 2022, 145 newly diagnosed, HIV-1-infected individuals in Baoding City were recruited into this study. The HIV-1 env gene sequence was successfully obtained from 142 of the 145 blood specimens, and the sequences were submitted to the Quality Control Tool (http//:HIV-DB Sequence Quality Control Tool (lanl.gov)) to analyze the viral subtype. The coreceptor tropism was predicted using the Geno2pheno web tool with falsepositive rate (FPR) values of 5%-15%, and the net charges of the third variable (V3) loop were calculated by Variable Region Characteristics (lanl.gov). The results showed that half of the patients were infected with the CCR5-tropic virus (50.0%, 71/142). In HIV-1 subtype CRF01_AE infection, the use of CXCR4 is expected to predominate, while in HIV-1 subtype CRF07_BC infection, CCR5 coreceptors are expected to be used predominantly. Sequence analysis of the V3 loop region revealed that subtypes CRF01_AE and CRF07_BC have similar median net charges (~3.0). Furthermore, GPGQ was found to be the major terminal tetrapeptide of the CRF07_ BC and CRF01_AE strains in this study. These findings enhance our understanding of the characteristics of the HIV-1 epidemic and provide important implications for HIV-1 vaccine design and clinical treatment.